Challenges in Heavy Flavor and Quarkonium Production in p + p Collisions at the LHC - Vogt R. (EPJ Web of Conferences, 2017)
I discuss new results and open challenges in open heavy flavor and quarkonium production in p + p collisions at the LHC.